Mechanical chest compression increases intrathoracic hemorrhage complications in patients receiving extracorporeal cardiopulmonary resuscitation - Yoshihisa Matsushima; Tatsuhiro Shibata; Kodai Shibao; Rei Yamakawa; Miyu Hayashida; Toshiyuki Yanai; Takashi Ishimatsu; Takehiro Homma; Shoichiro Nohara; Maki Otsuka; Yoshihiro Fukumoto (Resuscitation Plus)
Background: Mechanical cardiopulmonary resuscitation (CPR) devices address the limitations of manual CPR, but their impact on intrathoracic injuries during extracorporeal CPR (ECPR) remains unclear. This study investigated the relationship between mechanical CPR and severe intrathoracic hemorrhage during ECPR compared to manual CPR. Methods: We conducted a single-center retrospective study of consecutive patients who underwent ECPR from April 2017 to March 2024 according to a standard institutional protocol. Patients were divided into a mechanical CPR group (piston-driven compressions before veno-arterial extracorporeal membrane oxygenation [VA-ECMO]) and a manual CPR group. The primary outcome was intrathoracic hemorrhage requiring transcatheter arterial embolization (TAE). Secondary outcomes included other intrathoracic injuries and 180-day survival. Results: A total of 91 patients were enrolled (mechanical n = 48, manual n = 43). Intrathoracic hemorrhage requiring TAE occurred more frequently in the mechanical CPR group (18.8% vs. 2.3%, p = 0.030). On multivariate analysis, mechanical CPR was independently associated with this outcome (adjusted odds ratio 6.29; 95% confidence interval 1.20–65.10). In the mechanical group, older age and larger thoracic transverse diameter were significantly related to intrathoracic hemorrhage requiring TAE. Mediastinal hematoma (18.8% vs. 2.3%, p = 0.030) and hemothorax (20.8% vs. 4.7%, p = 0.049) were also more frequent in the mechanical group. The 180-day survival rates did not differ significantly between groups (27.7% vs. 25.0%, log-rank p = 0.540). Conclusions: Mechanical CPR during ECPR is associated with an increased risk of severe intrathoracic hemorrhage. While mechanical CPR devices may provide benefits in certain scenarios, clinicians should carefully consider individual patient characteristics and closely monitor for complications.